A flood risk management protocol for roads. Issue 4 (1st December 2014) - O'Malley, Vincent; Kitchen, Amanda; Dobson, Rene; Bryant, Ross; Hankin, Barry
Abstract : This paper reports on the development of a flood risk management protocol for the Irish National Roads Authority. There have been several extreme surface water flooding events across Ireland in recent times, causing wide-scale disruption, damage to the road network and loss of life. A fast, graphics-processor-based shallow water equation numerical scheme was used to model extreme surface water flooding for four design rainfall events covering the national road network to help understand key vulnerabilities and sensitivities of the network. Hazard data from these simulations were used to attribute short segments of carriageway and were combined with local traffic data to derive a disruption metric. A large suite of interactive maps was developed, combining the new surface water flood risk information with flood extents, other sources of flooding and historic records. These were incorporated into the protocol to help roads engineers prioritise locations for site visits, for which detailed site assessment sheets were developed. These focus further on the potential flooding mechanisms for culverts, bridges and drainage and are tabulated here, along with common mitigation strategies to assist the practitioner.